Exploring the relationships between team leader’s conflict management styles and team passion: From the emotional perspective - Yin, Jielin; Qu, Meng; Liao, Ganli; Jia, Muxiao; Li, Miaomiao (Frontiers in Psychology, 2022)
From the emotional perspective, this study explores how team leader’s conflict management styles affect team passion. A theoretical model is constructed which describes the mediating role of positive team emotional climate and the moderating impact of team emotional intelligence. We collect 101 teams paired data including 101 team leaders and 383 team members to test theoretical model. It is shown that leader’s cooperative conflict management style has a significant positive effect on both positive team emotional climate and team passion. Meanwhile, positive team emotional climate plays a mediating role between leader’s cooperative conflict management style and team passion. In addition, team emotional intelligence has a moderating effect between leader’s cooperative style and positive team emotional climate. This study not only provides a new perspective for follow-up research but also expands the research scope of impacts of conflict management styles. In addition, this study forms the underlying mechanism of team leader’s conflict management styles on team passion from the emotional perspective and investigates the mediating effect and moderating effect of emotional variable, which broadens the research on the mechanisms of conflict management styles on team outcomes to a certain extent.